Causes of variation orders in the Egyptian construction industry: Time and cost impacts - El Sarag, Jwanda Mohamed (AUC Knowledge Fountain, 2017)
Variation orders are of great significance in any construction project. Variation orders are defined as any change in the scope of works of a project that can result in an addition, omission, or even modification. This research introduces the variation orders that occur during construction in Egypt. The literature review involves a comparison of causes of variation orders in Egypt with Tanzania, Nigeria, Malaysia and the United Kingdom. A classification of occurrence of variation orders due to owner related factors, consultant related factors and other related factors are signified in the literature review. These classified events that lead to variation orders gathered from the literature review are introduced in a survey with 19 events to observe their frequency of occurrence, and their time and cost impacts. The survey data is obtained from 87 participants that included clients, consultants, and contractors. The number of participants in the survey is an acceptable representation of the population. A database of 42 scenarios is created that is used to develop an experts system model to help assist project managers in predicting the frequency of variations and account for a budget for any additional costs and minimize any delays that can take place. Two additional experts with more than 25 years of experience are given the expert system model to verify that it is working effectively. The model is then validated on a residential compound that was completed in July 2016 to prove that the model actually produces acceptable results.